Consequences of a Deficit in Vitamin B6 Biosynthesis de Novo for Hormone Homeostasis and Root Development in Arabidopsis . Issue 1 (4th December 2014) - Boycheva, Svetlana; Dominguez, Ana; Rolcik, Jakub; Boller, Thomas; Fitzpatrick, Teresa B.
Abstract : Deficits in de novo vitamin B6 biosynthesis impair hormone homeostasis and root development but are a consequence of differential regulation of the genes . Abstract: Vitamin B6 (pyridoxal 5′-phosphate) is an essential cofactor of many metabolic enzymes. Plants biosynthesize the vitamin de novo employing two enzymes, pyridoxine synthase1 (PDX1) and PDX2. In Arabidopsis ( Arabidopsis thaliana ), there are two catalytically active paralogs of PDX1 (PDX1.1 and PDX1.3) producing the vitamin at comparable rates. Since single mutants are viable but the pdx1.1 pdx1.3 double mutant is lethal, the corresponding enzymes seem redundant. However, the single mutants exhibit substantial phenotypic differences, particularly at the level of root development, with pdx1.3 being more impaired than pdx1.1 . Here, we investigate the differential regulation of PDX1.1 and PDX1.3 by identifying factors involved in their disparate phenotypes. Swapped-promoter experiments clarify the presence of distinct regulatory elements in the upstream regions of both genes. Exogenous sucrose (Suc) triggers impaired ethylene production in both mutants but is more severe in pdx1.3 than in pdx1.1 . Interestingly, Suc specifically represses PDX1.1 expression, accounting for the stronger vitamin B6 deficit in pdx1.3 compared with pdx1.1 . Surprisingly, Suc enhances auxin levels in pdx1.1, whereas the levels are diminished in pdx1.3 . In the case of pdx1.3, the previously reported reduced meristem activity combined with the impaired ethylene and auxin levels manifest the specific root developmental defects. Moreover, it is the deficit in ethylene production and/or signaling that triggers this outcome. On the other hand, we hypothesize that it is the increased auxin content of pdx1.1 that is responsible for the root developmental defects observed therein. We conclude that PDX1.1 and PDX1.3 play partially nonredundant roles and are differentially regulated as manifested in disparate root growth impairment morphologies.